HIGHER ECONOMIC EDUCATION IN CONCEPTS OF SYNERGETIC PARADIGM NONLINEAR THINKING - Tatiyana V. Kichkiruk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose is to investigate the potential of synergetic paradigm of nonlinear thinking to improve the quality of higher economic education in Ukraine. Methodology is based on the principles of objectivity, consistency, development of bottlenecks which allow investigating the existence of modern higher economic education in Ukraine due to the transitional stage of the country and worldwide globalization processes and crises associated with them. Scientific novelty. Synergetic paradigm nonlinear thinking is offered by the author as a promising alternative for getting out of this situation, to improve the quality of training in higher economic education. This will ensure that the conditions for the growth of the country's competitiveness internationally will improve the socio-economic situation in Ukraine. Conclusions. Modern economic education as a form of knowledge and learning requires active use of synergistic methods for its modernization and output to a new level of training future specialists and economists. In fact, synergy and self-organization becomes a modern paradigm of development and learning. Modern education strategy must reflect the ideas and principles of synergy.